Padronização, alinhamento e controle da formação e do trabalho docente no novo ensino médio em Santa Catarina: parceria da Secretaria do Estado da Educação com o Instituto IUNGO - Rodrigues, Erica (2023)
This work is part of the Research Line Society, Knowledge, and Education, of the Postgraduate Program in Education (PPGE) of the State University of Western Paraná (Unioeste, acronym in Portuguese), campus of Francisco Beltrão - PR. The main objective is to analyze the understanding of the teachers of the Basic Education School (EEB, acronym in Portuguese) Padre Antônio Vieira, located in the municipality of Ipuaçu - /SC concerning the processes of standardization, alignment, and control of training and teaching work implemented in the context of the New High School (NEM, acronym in Portuguese ) in the state of Santa Catarina (SC), in partnership with the Iungo Institute. To this end, the method chosen for the study was Historical and Dialectical Materialism. The research has a qualitative approach, to the case study type, with the development of bibliographic and documentary analyses on the proposal of NEM-SC for teacher training, which occurred from the virtual platforms of the Iungo Institute in partnership with the Secretary of Education of SC (SED-SC, acronym in Portuguese). In addition, a semi-structured interview was conducted to identify the understandings of teachers who participated in the implementation of NEM at EEB Padre Antônio Viera. As a result, we found that the current educational reforms undertaken through NEM-SC reveal the process of entrepreneurialization of education, as well as the implications of public-private partnerships forthe school. In this context, teacher training and work assume a prominent position, as there is an interest on the part of business reformers in controlling these fields (FREITAS, 2018). Since 2017, the state of Santa Catarina has been partnering with private institutions, such as IAS, or the third sector, such as the Iungo Institute, which define the content of education, through curriculares notebooks, the elaboration of portfolios that structure the flexible curriculum of the NEM, as well as the proposal for continuing education of public-school teachers. These actions ensure that teachers’ work is in line with the goals and guidelines established by the business sector. Given this scenario, the challenge is to continue studies and reflections to create strategies that dismantle the dictates of capital in its neoliberal form on school, training, and teaching work. In conclusion, it is agreed with Freitas (2018) that it is necessary to organize forms of resistance, such as the fight against the deprofessionalism of the teaching profession, ensuring adequate conditions for theoretical and practical training.